INVESTIGATING A GLOBALISED BUSINESS ENVIRONMENTS ON EXPORT PERFORMANCE - Huridi, Mohd Hanafia (International Journal of Psychosocial Rehabilitation, 2020)
A globalised business environment alongside with managerial characteristics, firm characteristics, and export marketing strategy on export performance are examined. This work focuses on both internal and external factors influence export performance that is reflected in two dominants theories: resource- based view (RBV) theory and contingency approach (CT). The RBV theory deals with internal factors, which are advantageously managed by firms like managerial characteristics, firm characteristics, and export marketing strategy, while the letter theory linked to external factors in view of a vibrant business environment. The outcome indicates that a globalised business environment, managerial characteristics, firm characteristics, and export marketing strategy significantly influence the export performance. The results of this work will be valuable guidance for the SMEs and decision makers in export business.